Predictors of complications following alloplastic cranioplasty in trauma patients: A multi-center retrospective study - Jingguo Yang; Junjie Wang; Chao You; Lu Ma; Junwen Guan (PLoS ONE, 2025)
Object Although technically simple, cranioplasty following decompressive craniectomy is associated with high complication rates. Assessing the factors that contribute to these complications is essential. The study aimed to present the complications following alloplastic cranioplasty in trauma patients and evaluate the factors that predispose patients to an increased risk of complications. Methods The author retrospectively reviewed cranioplasty cases at three institutions following craniectomy for trauma between 01/01/2018 and 31/12/2021. The risk factors included age, sex, smoking history, defect site, defect size, type of alloplastic materials, hydrocephalus after decompressive craniectomy (DC), hydrocephalus shunts before cranioplasty (CP), and the time interval between initial craniectomy and cranioplasty. The cranioplasty complications assessed were postoperative new-onset seizures, reoperation for hematoma, implant failure, and postoperative subgaleal effusion. Multivariate logistic regression analysis was performed to assess these risk factors. Results A total of 191 cranioplasties were included in this study, with a major complication rate of 26.2% (50 of 191). In multivariate analysis, the risk factors for major complications were smoking history, titanium cranioplasty, and a time interval to cranioplasty exceeding 3 months. Predictors of new-onset seizures in multivariate analysis included younger age, smoking history (OR = 4.69, p < 0.001), titanium cranioplasty (OR = 4.85, p = 0.049), and intermediate CP (OR = 5.46, p = 0.042). The rates of implant failure and postoperative hematoma were higher when cranioplasty was performed over 3 months or involved titanium cranioplasty. The rate of minor complication, specifically subgaleal effusion, was 18.9% (36 cases), with male sex being a significant variable in multivariate analysis. Conclusions This study presented complications and predictors of complications for cranioplasty in trauma patients, which could be incorporated with surgical decision-making for neurosurgeons.